Stable Carbon Isotopes Reveal Soil‐Stream DIC Linkages in Contrasting Headwater Catchments. Issue 1 (22nd January 2018) - Campeau, A.; Bishop, K.; Nilsson, M. B.; Klemedtsson, L.; Laudon, H.; Leith, F. I.; Öquist, M.; Wallin, M. B.
Abstract: Large CO2 evasion to the atmosphere occurs as dissolved inorganic carbon (DIC) is transported from soils to streams. While this physical process has been the focus of multiple studies, less is known about the underlying biogeochemical transformations that accompany this transfer of C from soils to streams. Here we used patterns in stream water and groundwater δ 13 C‐DIC values within three headwater catchments with contrasting land cover to identify the sources and processes regulating DIC during its transport. We found that although considerable CO2 evasion occurs as DIC is transported from soils to streams, there were also other processes affecting the DIC pool. Methane production and mixing of C sources, associated with different types and spatial distribution of peat‐rich areas within each catchment, had a significant influence on the δ 13 C‐DIC values in both soils and streams. These processes represent an additional control on δ 13 C‐DIC values and the catchment‐scale cycling of DIC across different northern landscape types. The results from this study demonstrate that the transport of DIC from soils to streams results in more than just rapid CO2 evasion to the atmosphere but also represents a channel of C transformation, which questions some of our current conceptualizations of C cycling at the landscape scale. Plain Language Summary: Large carbon dioxide emission to the atmosphere occurs as rainwater percolates through soils and into streams. This physical process is important for the global carbon cycle and has been the focus of multiple studies. However, less is known about the underlying processes that accompanies this transfer of carbon dioxide from soils to streams. Here we analyze the stable isotope composition of soil and stream carbon dioxide and demonstrate that methane production and mixing of carbon sources also occur in soils and streams. These processes were linked to different types and configurations of peat‐rich areas, for example, bogs, fens, and riparian zones, found within each of the three studied catchments. Our results therefore demonstrate that the export of carbon dioxide from soils to streams not only results in emissions to the atmosphere but also represents a channel of transformation. This questions some of our current conceptualization of the catchment‐scale cycling of carbon dioxide. Key Points: We present one of the first comparative data sets of stream water and groundwater δ 13 C‐DIC values from contrasting headwater catchments DIC transport from soils to streams not only entails considerable CO2 emissions but is also a channel for C transformation and mixing of sources Methanogenesis plays a considerable role in the catchment‐scale cycling of DIC within specific ecosystem types